Pengujian Efikasi Antimikroba Ekoenzim terhadap Staphylococcus aureus dan Escherichia coli sebagai Aktivitas Partisipatif Siswa dalam Materi Bioteknologi untuk Pengelolaan Limbah Makanan - Fina Nurul Arifah; Eka Cahya Prima (Institut Agama Islam Negeri Kerinci, 2025)
This study investigates the antimicrobial efficacy of eco-enzymes derived from organic waste, specifically fruit and vegetable peels, against Escherichia coli and Staphylococcus aureus bacteria. Eco-enzymes were produced through a simple fermentation process involving kitchen scraps, brown sugar, and water. Antibacterial activity was evaluated using agar diffusion assays, where different concentrations of eco-enzymes were tested against bacterial cultures. Results showed significant inhibition zones, indicating effective antimicrobial properties against both bacterial strains. Higher concentrations of eco-enzymes correlated with larger inhibition zones, highlighting their potential as natural alternatives for bacterial control in various applications, including food processing and wastewater treatment. Furthermore, eco-enzymes contribute to sustainable organic waste management by converting waste into useful bio-sanitizers, floor cleaners, bio-pesticides, and plant fertilizers. This research underscores the dual benefits of eco-enzymes in reducing environmental impact and promoting sustainable development goals.